2017
DOI: 10.1177/1010428317697552
|View full text |Cite
|
Sign up to set email alerts
|

Predictive role of serum and urinary cytokines in invasion and recurrence of bladder cancer

Abstract: Urothelial cancer patients are prone to recurrence, and there is no marker to predict which cases become refractory to the immunotherapy given to these patients. Tumour behaviour is decided by the dynamics between the pro-and antitumorigenic cytokines. In this study, 27 cytokines were estimated in serum and urine of 72 urothelial cancer patients and 42 healthy volunteer controls. Serum cytokines IL-1RA, IL-4 and RANTES were in significantly higher concentration in serum of patients compared to controls, while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
42
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 28 publications
4
42
0
2
Order By: Relevance
“…However, in accordance with other studies, we found that using urine COL4A1 and COL13A1 concentration normalized to urine creatinine (ng/mg Cre) instead of urinary concentration alone (ng/mL) did not improve the diagnostic accuracy. Our results are similar to those of other urinary protein‐based tests, aiming for measurement of soluble proteins related to BCa; for instance, analysis of growth factors, matrix metalloproteases, or other cytokines in urine . The greater the progression of the BCa, the higher the urine collagen concentration and detection sensitivity (Tables ).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…However, in accordance with other studies, we found that using urine COL4A1 and COL13A1 concentration normalized to urine creatinine (ng/mg Cre) instead of urinary concentration alone (ng/mL) did not improve the diagnostic accuracy. Our results are similar to those of other urinary protein‐based tests, aiming for measurement of soluble proteins related to BCa; for instance, analysis of growth factors, matrix metalloproteases, or other cytokines in urine . The greater the progression of the BCa, the higher the urine collagen concentration and detection sensitivity (Tables ).…”
Section: Discussionsupporting
confidence: 84%
“…As Kumari et al . reported, a panel of serum cytokines had a predictive role in the invasion and recurrence of BCa; serum can be a useful source of non‐invasive diagnostic and prognostic biomarkers for BCa. Kang et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to our results, Kumari et al reported that urine level of GM-CSF was significantly higher in high-grade bladder cancer patients compared to low-grade bladder cancer patients and controls. 26 In the present study, all the patients were diagnosed with high-grade bladder cancer. GM-CSF in the urine of patients with bladder cancer may indicate poor prognosis.…”
Section: Discussionmentioning
confidence: 86%